Strategi pemasaran bisnis kuliner menggunakan influencer di media sosial instagram pasca pandemi - Reziyana Hardini; Mentari Iffa Nurani; Faradita Larasayu; Erwin Permana (Jurnal Riset Pendidikan Ekonomi, 2023)
Competition in the culinary sector is increasingly rife, requiring business people to be able to always use marketing strategies that are relevant to the times.  One marketing strategy that has become increasingly popular lately is using influencers.  Through their influence on social media, influencers can endorse a product that is becoming increasingly popular.  An influencer will usually endorse a variety of products.  Therefore, research on influencers who endorse only one type of product has not been carried out much, in this case the Semarang lumpia product.  This study aims to analyze marketing strategies for culinary businesses using influencers on post-pandemic Instagram social media.  The study uses a descriptive qualitative approach. The research data were obtained through observation of influencer accounts that endorse Lumpia Semarang products.  To support data analysis, various supporting sources were extracted, such as publications on various official and popular sites.  The results of the study concluded that the marketing strategy carried out by one of the culinary business actors, namely lumpiasemarang.jkt, using influencers was very effective because it aroused and aroused consumer curiosity to try this culinary.  The influencers used are included in the macro influencer category such as half of the fat which is an influencer with many followers who are already popular with many groups so that they are able to popularize Lumia Semarang cuisine among Indonesian people.